A Pilot Study of Peripheral Muscle Magnetic Stimulation as Add-on Treatment to Repetitive Transcranial Magnetic Stimulation in Chronic Tinnitus - Vielsmeier, Veronika; Schecklmann, Martin; Schlee, Winfried; Kreuzer, Peter M.; Poeppl, Timm B.; Rupprecht, Rainer; Langguth, Berthold; Lehner, Astrid (Frontiers in Neuroscience, 2018)
While brain stimulation techniques have been examined as treatment options for chronic tinnitus for many years, they have recently been extended to multimodal treatment approaches. As chronic tinnitus is often accompanied by comorbid muscular tension in the neck and back, we performed a one-arm pilot study to explore the feasibility of a new multimodal treatment approach. In detail, repetitive peripheral magnetic stimulation (rPMS) of the back was performed before and after each session of repetitive transcranial magnetic stimulation (rTMS) of the brain. Data of 41 patients were analysed, all of which were treated with ten sessions of rTMS of the left prefrontal and left temporoparietal cortex followed by rPMS of the neck and back muscles. Tinnitus severity was measured using the tinnitus questionnaire (TQ). Neck pain was assessed using the neck pain and disability scale (NPAD). The new treatment approach was feasible and well accepted by the majority of patients. However, the overall patient group did not improve significantly in either of the questionnaires. If patients were divided in different subgroups depending on whether they were suffering from neck pain or somatosensory tinnitus, explorative post-hoc tests suggested differential effects: patients with both neck pain and somatosensory tinnitus had better outcomes than patients without those conditions or with neck pain only. This was true for both the TQ and the NPAD. This effect was of transient nature though: the TQ score went back to its baseline level after a follow-up period of 12 weeks. Based on our results we recommend that in studies that investigate tinnitus treatments targeting somatosensory afferents patients should be stratified according to somatic co-morbidities and somatosensory influence on the tinnitus percept. The study was registered at www.clinicaltrials.gov. (NCT02306447).